2017
DOI: 10.1016/j.ajog.2016.11.1033
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node assessment in endometrial cancer: a systematic review and meta-analysis

Abstract: Sentinel lymph node mapping is feasible and accurately predicts nodal status in women with endometrial cancer. The current data favors the use of cervical injection techniques with indocyanine green. Sentinel lymph mapping may be considered an alternative standard of care in the staging of women with endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
150
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(169 citation statements)
references
References 70 publications
14
150
2
3
Order By: Relevance
“…The results of the SENTI-ENDO and FIRES studies were supported by a large meta-analysis study 37. Among nearly 5000 patients from 55 accumulative studies, the sensitivity of SLN mapping in detecting metastatic disease reached 96% with a pooled negative predictive value of 99.7%.…”
Section: Establishing the Accuracy Of Sln Biopsy For Endometrial Cancermentioning
confidence: 86%
“…The results of the SENTI-ENDO and FIRES studies were supported by a large meta-analysis study 37. Among nearly 5000 patients from 55 accumulative studies, the sensitivity of SLN mapping in detecting metastatic disease reached 96% with a pooled negative predictive value of 99.7%.…”
Section: Establishing the Accuracy Of Sln Biopsy For Endometrial Cancermentioning
confidence: 86%
“…Sentinel lymph node mapping has been introduced into the surgical staging of endometrial cancer with the goal to reduce morbidity associated with comprehensive lymphadenectomy and to obtain prognostic information from lymph node status. A recent meta‐analysis reported overall detection rates higher than 80%, with 50% bilateral pelvic node detection rate and 17% para‐aortic detection rate . Use of indocyanine green increases the bilateral detection rate compared with blue dye.…”
Section: Is Lymphadenectomy Therapeutic?mentioning
confidence: 99%
“…While SLN mapping is standard practice for other solid tumors such as breast cancer and melanoma, lymphatic mapping in endometrial cancer is not without controversy. This controversy stems from the wide variability of bilateral SLN mapping rates observed in the literature, as well as continued uncertainty about optimal injection strategy 3. In a recently completed prospective trial (FIRES) evaluating the false-negative rate of SLN mapping using indocyanine green dye for endometrial cancer, SLNs were identified bilaterally in only 52% of patients.…”
Section: Introductionmentioning
confidence: 99%